2001
DOI: 10.1016/s0944-5013(01)80004-5
|View full text |Cite
|
Sign up to set email alerts
|

Detection and characterization of quorum sensing signal molecules in Acinetobacter strains

Abstract: Quorum sensing is a widespread regulatory mechanism among Gram-negative bacteria. In this study, Acinetobacter strains were assayed for the presence of quorum sensing signal molecules capable of activating N-acylhomoserine lactone biosensors. By using an Agrobacterium tumefaciens reporter strain it was shown that all the cultures produced two to four detectable signal molecules with different chromatographic patterns. In A. calcoaceticus BD413 supernatants four compounds were detected in a time-dependent manne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
42
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(44 citation statements)
references
References 22 publications
1
42
0
1
Order By: Relevance
“…Finally, quorum sensing has been shown to regulate a wide array of virulence mechanisms in many gram-negative organisms, particularly P. aeruginosa. Up to four different quorum-sensing signal molecules have been identified in Acinetobacter, indicating that this may be a central mechanism for autoinduction of multiple virulence factors (203,271).…”
Section: Host-pathogen Interactions Involving Acinetobactermentioning
confidence: 99%
“…Finally, quorum sensing has been shown to regulate a wide array of virulence mechanisms in many gram-negative organisms, particularly P. aeruginosa. Up to four different quorum-sensing signal molecules have been identified in Acinetobacter, indicating that this may be a central mechanism for autoinduction of multiple virulence factors (203,271).…”
Section: Host-pathogen Interactions Involving Acinetobactermentioning
confidence: 99%
“…18 In A. baumannii, N-(3-hydroxydodecanoyl)-l-homoserine lactone (3-hydroxy-C12-HSL) is the only quorum sensing molecule identified, though mass spectrometry suggested that other AHL molecules are also present at significantly lower amounts. [19][20][21] However,contribution of quorum sensors and iron concentration to the overall pathogenic potential in the genus is currently unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Using these biosensors, previous studies showed AHL production by Acinetobacter spp. (15). In a variety of gram-negative bacteria, it has also been demonstrated that biofilm development can be dependent on AHL signaling (7,18,26).…”
mentioning
confidence: 99%